Is the Mean Platelet Volume in Patients with Acute Cholecystitis an Inflammatory Marker? - Sayit, Asli Tanrivermis (J Clin Diagn Res, 2015)
INTRODUCTION: Acute cholecystitis is an inflammatory disease of the gallbladder. Ultrasonography (US) is the initial and the most valuable method in the diagnosis of acute cholecystitis. Also, laboratory findings are used to support the diagnosis. The aim of the present study was to evaluate the diagnostic value of mean platelet volume (MPV) and platelet (PLT) counts in patients with acute cholecystitis. MATERIALS AND METHODS: From January to August 2014, the medical records of patients were reviewed for the diagnosis of acute cholecystitis. The study included 60 age-matched patients with acute cholecystitis and 60 healthy individuals as a control group. Patients with a chronic disease were excluded from the study. Over all, patients with acute cholecystitis and patients in the control group were evaluated for their MPV, PLT count, platelet distribution width (PDW), platelet crit (PCT) and erythrocyte sedimentation rate (ESR) in a complete blood count (CBC). RESULTS: The MPV values were found to be significantly lower in the acute cholecystitis group when compared to the control group. The PDW and PCT were found to be significantly higher in the acute cholecystitis group when compered to the control group. When a correlation test was performed, MPV was negatively correlated with PLT and PCT counts. CONCLUSION: US is the initial and the most important imaging method for diagnosing and evaluating the biliary system. Also, laboratory findings such as WBC, ESR and CRP support the diagnosis but may have some undesirable limitations. However, MPV is an acute phase reactant that does not require an additional cost because it is already worked in the CBC. Therefore, MPV can be used as a marker in diagnosing inflammatory diseases.